International experiences in developing intercultural competence in pre-service teacher education programs - Abdullayeva, Nilufar (The Lingua Spectrum, 2026)
This article analyzes international experiences in developing intercultural communicative competence in pre-service teacher education programmes. In particular, it examines theoretical and practical studies related to Morocco, Taiwan, Oman, Spain, virtual exchange projects, study abroad programmes, and European initiatives.